Effect of folate supplementation on mucosal cell proliferation in high risk patients for colon cancer. Issue 2 (1st August 2002) - Khosraviani, K; Weir, H P; Hamilton, P; Moorehead, J; Williamson, K
Abstract : Aims: Intracellular folate deficiency has been implicated in colonic carcinogenesis in epidemiological studies and animal and human cancer models. Our aim was to determine the effect of folate supplementation on patients with recurrent adenomatous polyps using rectal mucosal cell proliferation as a biomarker. Patients and methods: Eleven patients with recurrent adenomatous polyps of the colon were randomised into a treatment group (n=6) receiving a dietary supplement of 2 mg folic acid per day for three months and a control group (n=5) receiving a placebo. Rectal biopsies where taken at 10 cm from the anal verge prior to supplementation and repeated at four, 12, and 18 weeks from the start of the supplementation. Each biopsy was immediately incubated in culture medium enriched with bromodeoxyuridine (BrdU). The S phase cells which incorporated BrdU into their DNA were identified following immunohistochemical staining. Twenty five orientated crypts were identified for each time point and the number and position of BrdU positive and BrdU negative cells were counted. BrdU labelling indices (LIs) were calculated for the entire crypt and for each of five equal compartments running consequently from the base to the luminal surface. Results: The LI of the treatment group (9.1 (6.7, 12.3)) and the control group (9.3 (7.8, 10.3)) were comparable at the start. Over the duration of the supplementation period, LI in the control group did not alter significantly (9.3 (7.8, 10.3) v 9.6 (8.9, 10.4)). However, LI of the folate treated group was lowered after 12 weeks of supplementation (9.1 (6.7, 12.3) v 7.4 (5.3, 9.6)). Analysis of the LI for compartments within the crypt showed that the most significant drop in number of proliferating cells was in the upper most regions of the crypt. Conclusion: These data indicate that (a) folate supplementation decreases colonic mucosal cell proliferation in a high risk group for colon cancer and (b) the most significant reduction takes place at the luminal aspect of the crypt.